Bacterial removal of sulfur from the China lignite by a newly isolated bacterium, Sinomonas flava XL4. Issue 2 (9th August 2015) - Liu, Tong; Hou, Jinhui; Peng, Yaoli
Abstract : The lignite coal collected from Shengli coalfield of Inner Mongolia Autonomous Region in China contains about 5.22% by mass total sulfur with a gross calorific value of 6329 cal g −1 . In the present work, the coal sample was subjected to desulfurization by using a new bacterium isolated from the native coal mine site. The native bacterium was identified to be Sinomonas flava XL4 based on the 16S rDNA gene sequence analysis, and reported first time for the capability to remove about 44% of total sulfur from the lignite coal. The influence of various process parameters such as medium pH, incubation time, pulp density, particle size, incubation temperature on sulfur removal from the lignite after S. flava XL4 treatment was investigated, and the experimental results showed that the total sulfur content of lignite coal was reduce to 2.92% under optimum reaction conditions. In addtion, the calorific value of lignite coal after bacterium desulfurization increased from 6329 to 6678 cal g −1, and the ash content was eliminated. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 374–379, 2016